2022
DOI: 10.3233/shti220765
|View full text |Cite
|
Sign up to set email alerts
|

Using Association Rules in Antimicrobial Resistance in Stone Disease Patients

Abstract: Association rule mining is a very popular unsupervised machine learning technique for discovering patterns in large datasets. Patients with stone disease commonly suffer from urinary tract infections (UTI), complicated by the emergence of antimicrobial resistance (AMR), due to the excessive use of antibiotics. In this study, we explore the use of association rule mining in the AMR profile of patients suffering from stone disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
0
1
0
Order By: Relevance
“…Nevertheless, ChatGPT is capable of learning from proper inputs, as demonstrated by Manolitsis et al . [20]. In their study with a custom-training program for ChatGPT, they found that by training the models with very specific content on the individuals, the credibility of the information received is increased.…”
Section: Enhancing Efficiencymentioning
confidence: 99%
“…Nevertheless, ChatGPT is capable of learning from proper inputs, as demonstrated by Manolitsis et al . [20]. In their study with a custom-training program for ChatGPT, they found that by training the models with very specific content on the individuals, the credibility of the information received is increased.…”
Section: Enhancing Efficiencymentioning
confidence: 99%
“…Association Rules associate a specific conclusion with a set of conditions. In comparison to standard decision tree algorithms such as the C5.0 and C&R trees, the associations can occur between any of the variables [53][54][55].…”
Section: Association Analysesmentioning
confidence: 99%
“…Practitioners could input patient comorbidities and receive monitoring support aligned with patient specific evidence-based local and national guidelines 20 . Moreover, users can understand the evidence and rationale behind each prompt, enriching their learning with each interaction.…”
Section: Accepted Manuscriptmentioning
confidence: 99%